Assessing the Texas Christian University Drug Screen Instrument with Texas Department of Criminal Justice Inmates, 1999-2000 - Knight, Kevin D. ([Verlag nicht ermittelbar], 2003)
The overall purpose of this study was to examine the psychometric properties and credibility of the Texas Christian University (TCU) Drug Screen as an instrument to assess drug use severity for treatment referral decisions in correctional settings. TCU Drug Screen data were collected on 18,364 Texas Department of Criminal Justice (TDCJ) inmates (15,816 males and 2,548 females) who completed the screen between January 1 and April 30, 1999. Of the 18,364 subjects, 13,902 were Institutional Division (TDCJ-ID) inmates and 4,462 were State Jail Division (TDCJ-SJD) inmates. The TCU Drug Screen was administered by TDCJ staff almost exclusively in a small group setting (12-25 inmates per group) as part of a larger battery of assessments during the intake process at a TDCJ facility. The level and intensity of treatment services needed was then determined and a referral decision was made. As part of this study, the relationship between TCU Drug Screen information and post-release reincarceration was examined. Although one original goal in the study was to assess the comparability, or concurrent validity, of the TCU Drug Screen with the lengthier, more comprehensive Addiction Severity Index (ASI), TDCJ changed the administration protocol for the ASI so that it was given only to a subsample of 3,245 inmates who failed to disclose drug use problems on the TCU Drug Screen. The data include inmate responses to all items of the TCU Drug Screen and the overall drug screen score. There is also demographic information as well as incarceration, release, and reincarceration data.